An atlas of subgroup lattices of finite almost simple groups - Connor, Thomas (Ars mathematica contemporanea, 2015)
We provide algorithms to compute and produce subgroup lattices of finite permutation groups. We discuss the problem of naming groups and we propose an algorithm that automatizes the naming of groups, together with possible ways of refinement. Finally we announce an atlas of subgroup lattices for a large collection of finite almost simple groups made available online.
Keywords: computational methods in group theory; lattices of subgroups; mreža podgrup; računske metode v teoriji grup